TrkAIII signals endoplasmic reticulum stress to the mitochondria in neuroblastoma cells, resulting in glycolytic metabolic adaptation - Farina, Antonietta Rosella (Oncotarget, 2017)
Alternative TrkAIII splicing characterises advanced stage metastatic disease and post-therapeutic relapse in neuroblastoma (NB), and in NB models TrkAIII exhibits oncogenic activity. In this study, we report a novel role for TrkAIII in signaling ER stress to the mitochondria in SH-SY5Y NB cells that results in glycolytic metabolic adaptation. The ER stress-inducing agents DTT, A23187 and thapsigargin activated the ER stress-response in control pcDNA SH-SY5Y and TrkAIII expressing SH-SY5Y cells and in TrkAIII SH-SY5Y cells increased TrkAIII targeting to mitochondria and internalisation into inner-mitochondrial membranes. Within inner-mitochondrial membranes, TrkAIII was subjected to Omi/HtrA2-dependent cleavage to tyrosine phosphorylated 45–48kDa carboxyl terminal active fragments, localised predominantly in tyrosine kinase-domain mitochondrial matrix orientation. This stress-induced activation of mitochondrial TrkAIII was associated with increased ROS production, prevented by the ROS scavenger Resveratrol and underpinned by changes in Ca2+ movement, implicating ROS/Ca2+ interplay in overcoming the mitochondrial TrkAIII activation threshold. Stress-induced, cleavage-activation of mitochondrial TrkAIII resulted in mitochondrial PDHK1 tyrosine phosphorylation, leading to glycolytic metabolic adaptation. This novel mitochondrial role for TrkAIII provides a potential self-perpetuating, drug reversible way through which tumour microenvironmental stress may maintain the metastasis promoting “Warburg effect” in TrkAIII expressing NBs.